Kejahatan Korporasi Suatu Fenomena Lama Dalam Bentuk Baru - Reksodiputro, Mardjono Mardjono Reksodiputro (Indonesian Journal of International Law, 2021)
The economic crisis in 1997 has confirmed the Indonesian society that white collar criminality also exist in their country. The failure to bring the corporate criminals to court was caused by the difficult of the Indonesian justice system to accept that corporations can also be held accountable under the Indonesian criminal law. On the other hand, legislature has accepted that corporations (as juristic persons) can be held liable, beside the managers (as natural persons). Since 1995, law no. 7 on economic crimes also include juristic persons as subjects of the law. This has been followed by the legislature in 1963 (law on subversion), 1976 (law on drug abuse) and 1997 (law on the environment). In 1993 a draft of the newPenal Code for Indonesia was submitted to the Minister of Justice. No step have been taken yet to implement the code, which in article 44 explicitly states that corporations can be held responsible for criminal acts. With respect to a law enforcement strategy against corporate crimes, the author wishes to distinguish between organized crimes and crimes by organizations. Both can be done by or through corporation.